Collusion Through Joint R&D: An Empirical Assessment - Duso, Tomaso; Röller, Lars-Hendrik; Seldeslachts, Jo (The Review of Economics and Statistics, 2014)
This paper tests whether upstream R&D cooperation leads to downstream collusion. We show that a sufficient condition for identifying collusive behavior is a decline in the market share of firms participating in research joint ventures (RJVs). Using information from the U.S. National Cooperation Research Act, we estimate a market share equation correcting for the endogeneity of RJV participation and R&D expenditures. We find robust evidence that large networks between direct competitors, created through firms being members in several RJVs at the same time, are conducive to collusive outcomes in the product market that reduce consumer welfare. By contrast, RJVs among noncompetitors are efficiency enhancing.